Advanced training for researchers in Ethiopia on sheep and goat semen cooling technique - Rekik, Mourad; Getachew, Tesfaye (International Center for Agricultural Research in the Dry Areas, 2023)
A two-day advanced training session on semen cooling technique was conducted at the Doyogena CBBP site in Ethiopia. The training specifically targeted researchers involved in implementing sheep and goat CBBPs. In Ethiopia, ICARDA and its partners, under the previous CRP program, established ten low-cost reproductive technology laboratories across different regions. These laboratories are equipped with mobile equipment for semen collection, evaluation, and insemination for sheep and goats. More information about these labs can be found at Low-Cost, Mobile Reproductive Labs for Better Sheep and Goat Breeding | ICARDA. Artificial insemination has been implemented as a means of disseminating improved genetics within the CBBPs and surrounding sheep and goat flocks, known as production units. Artificial insemination offers several advantages in advancing genetic progress, including increased selection intensity, enhanced parental control, improved reproductive management, and prevention of spreading reproductive diseases. So far, small ruminant artificial insemination in Ethiopia relied on collecting fresh semen, processing it, and immediately inseminating the females; the whole process should be carried out at relatively constant temperatures between 37 and 35 ˚C and the time separating semen collection from deposition should not exceed 20-30 minutes. However, the introduction of semen cooling down to around 15-17 ˚C brings about significant benefits. Cooling semen extends its shelf life, provides increased access to superior genetics for farmers in distant locations from the improved sires, offers flexibility in organizing inseminations by separating them spatially from semen production, democratizes access to genetics for farmers in distant villages and results in cost savings. This valuable technique contributes to further optimization of the breeding schemes, enhances genetic selection, and improves the overall performance of flocks. Under the SAPLING initiative, four specialized semen coolers have been made available and distributed to the Menz, Bonga, and Doyogena CBBP sites. The semen cooling boxes allow for the preservation for 4 to 6 hours of semen from the best rams in different CBBP villages, which can then be transported to distant locations for insemination. This centralized approach streamlines the process and facilitates the dissemination of superior genetics. Overall, this training on semen cooling and the availability of specialized semen coolers through the SAPLING initiative marks a significant advancement in sheep and goat breeding practices in Ethiopia, enabling the utilization of improved genetics and enhancing the overall productivity of the flocks in the CBBP nucleus and in the production units. This report provides a summary of the two-day training session on the utilization of semen cooling techniques. The training took place in the Doyogena CBBP village in Ethiopia and was attended by researchers from various regions across the country.